Broadcasting strategies in 6TiSCH networks. Issue 1 (30th November 2017) - Vučinić, Mališa; Watteyne, Thomas; Vilajosana, Xavier
Abstract : We consider IPv6‐enabled networks that run on top of the time‐slotted channel hopping mode of IEEE802.15.4 (6TiSCH). The ongoing discussions in the standardization community concern the network formation process and the definition of a bootstrapping protocol by which a new mote is admitted into the network. Because the bootstrapping traffic uses the same shared slots as the network broadcasts, the key to the optimal performance of the network formation process lays in the optimization of the network broadcasting strategy. The problem boils down to the issue of stabilizing slotted Aloha. To do so, we adapt a broadcast algorithm to the specifics of 6TiSCH networks. By simulation, we evaluate the optimal broadcast transmission probability in the network. We answer the open questions in the IETF 6TiSCH standardization community that concern the performance of the network formation process for the optimal values of transmission probability. As the main contribution of the letter, we provide network administrators with a set of values that allow the formation of dense networks.